Labor productivity - Dunlop, John T.; Diatchenko, Vasilii P.; International Economic Association (New York : McGraw-Hill, 1964)
The Conference on Labor Productivity, held at Cadenabbia, Lake Como, Italy, August 31 to September 8, 1961, brought together approximately 40 economists, equally divided between Western and Eastern countries to discuss in scientific terms various aspects of labor productivity. Thirty papers were prepared for the Conference. These papers were discussed during ten sessions with the assistance of simultaneous translation in English and Russian. The papers are divided into four parts. Part I: Concepts and Measurement of Productivity. Part II: International Comparisons of Productivity. Part III: Wages and Productivity. Part IV: Technical, Managerial and Organizational Factors Affecting Productivity.
It was the decision of the Program Committee that Prof. Dunlop be responsible for the English ed. and the Prof. Diatchenko be responsible for the Russian ed.
"[Met] under the auspices of the International Economic Association."
Includes bibliographical references.
rpm 05/04/2018
Loans
Keywords: Labor productivity